Penyuluhan Hukum dan Pendampingan Sistem Kemitraan untuk Meningkatkan Kemandirian Kelompok Usaha di Masyarakat - Anugrah Haryata Pratama; Rofik Priyanto; Rizal Rifai; Dwi Nur Hidayat (Institut Teknologi dan Bisnis Semarang, 2025)
In order to encourage sustainable regional economic growth, the independence of community business groups is very important. The purpose of this initiative is to improve legal literacy, understanding of the partnership system, and independent business management in regional business associations. On November 11, 2024, 25 people participated in this activity for the Berkah Mendo Farmer Group in Banjarnegara Regency. The results of the implementation showed the effectiveness of legal counseling in increasing legal awareness of business actors, so that they were able to understand their rights and obligations in running a business. Partnership system assistance provides useful input in creating fair and sustainable business partnerships, and strengthens the theory of business collaboration that emphasizes the importance of equality and transparency. Theoretical reflection emphasizes that, in accordance with the principle of community empowerment, business organizations can be strengthened through an empowerment approach based on legal literacy and strategic partnership practices. In short, this initiative not only directly affects the independence of business groups but also serves as an example that can be used by other areas with comparable characteristics. It is hoped that by implementing these suggestions, an independent, competitive, and sustainable communal economic ecosystem will be formed.